Nilai Estetika Buku Teks Kurikulum 2013 Edisi Revisi 2019 Kelas I Ditinjau Dari Persepsi Guru MIN 1 Bantul - Pangestu Cahyo Gumelar; Sedya Santosa (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Teaching materials are a set of learning tools or tools that are very important in advancing education. Teaching materials in their role are also responsible for the quality of learning in Madrasah / Schools which need to be continuously developed according to the needs of the times. As teaching materials, of course, textbooks not only content material, but also need methods, limitations, and ways of evaluating that are systematically designed and interesting to achieve the expected goals. In the matter of attracting interest in the use of this textbook, of course, it does not escape the aesthetic elements contained in this textbook. The teacher as the front guard in applying thematic textbooks, of course, understands very well what students need to face the changing times. Therefore, the quality in thematic textbooks needs to be known through the views or perceptions of the classroom teachers. This research is field research (field research) which is a combination (mix method) The combined research method is qualitative and quantitative so that the data obtained is more comprehensive and objective. . The subjects of this study were all first-grade teachers of MIN 1 Bantul, and the object of this study was the 2019 revised edition of thematic textbooks. The results of this study according to the teacher's perceptions were very feasible.